The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/aogs.14018
|View full text |Cite
|
Sign up to set email alerts
|

Single‐ or double‐layer uterine closure techniques following cesarean: A randomized trial

Abstract: Introduction Cesarean deliveries are commonly performed throughout the world. Although the uterine closure technique following this procedure may influence how the uterine scar heals, there is insufficient evidence for choosing the appropriate technique and so preventing long‐term negative consequences. This prospective, randomized study examined the effects of single‐ and double‐layer uterine closure techniques on uterine scar healing following cesarean delivery. Material and methods This study assessed a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Although the DL closure showed better sonographic outcomes, as revealed by the present study and previous studies [ 9 ], these outcomes seem to be clinically insignificant [ 8 , 28 ]. Thus, SL closure is still the most popular method for uterine closure after CS delivery.…”
Section: Reviewsupporting
confidence: 68%
See 3 more Smart Citations
“…Although the DL closure showed better sonographic outcomes, as revealed by the present study and previous studies [ 9 ], these outcomes seem to be clinically insignificant [ 8 , 28 ]. Thus, SL closure is still the most popular method for uterine closure after CS delivery.…”
Section: Reviewsupporting
confidence: 68%
“…However, a recent trial reported similar rates with both techniques [ 8 ]. In our study, the superiority of the DL closure method was attributed to the recent trial by Yilmaz Baran 2020 [ 28 ], while the other pooled trials showed insignificant results [ 3 , 15 , 22 ]. Thus, the present study solves this debate in favor of the DL closure technique by pooling the results of all previously published RCTs.…”
Section: Reviewmentioning
confidence: 59%
See 2 more Smart Citations
“…The etiology of CSD has yet to be fully elucidated because conclusive data are lacking. Notably, it is unclear whether a double‐layer suture of the uterine incision is better than a single‐layer suture 12,13 . In particular, there is a lack of research on patient‐related factors such as infection and genetic differences, which may be underestimated 14 .…”
Section: Introductionmentioning
confidence: 99%